Autoimmune Pemphigus: Latest Advances and Emerging Therapies - Lim, Yen Loo; Bohelay, Gerome; Hanakawa, Sho; Musette, Philippe; Janela, Baptiste (Frontiers in Molecular Biosciences, 2022)
Pemphigus represents a group of rare and severe autoimmune intra-epidermal blistering diseases affecting the skin and mucous membranes. These painful and debilitating diseases are driven by the production of autoantibodies that are mainly directed against the desmosomal adhesion proteins, desmoglein 3 (Dsg3) and desmoglein 1 (Dsg1). The search to define underlying triggers for anti-Dsg-antibody production has revealed genetic, environmental, and possible vaccine-driven factors, but our knowledge of the processes underlying disease initiation and pathology remains incomplete. Recent studies point to an important role of T cells in supporting auto-antibody production; yet the involvement of the myeloid compartment remains unexplored. Clinical management of pemphigus is beginning to move away from broad-spectrum immunosuppression and towards B-cell-targeted therapies, which reduce many patients’ symptoms but can have significant side effects. Here, we review the latest developments in our understanding of the predisposing factors/conditions of pemphigus, the underlying pathogenic mechanisms, and new and emerging therapies to treat these devastating diseases.